Mobilising equity. Emerging evidence for integrating vulnerable communities - Di Ruocco, Irina (TeMA - Journal of Land Use, Mobility and Environment, 2025)
The transition towards sustainable cities is progressing, with numerous smart city technologies and innovative concepts being implemented. However, these advancements have predominantly focused on urban areas, often overlooking the critical need for integrating transportation systems with surrounding rural regions. Equitable access for vulnerable populations in peripheral areas remains underexplored, with most research focusing on the elderly while neglecting other vulnerable groups such as ethnic and gender minorities, women, young people, and individuals with serious health conditions. Empirical evidence shows that many rely on private transportation or are confined to small, localized areas. This article, through a literature review, analyses emerging research evidence on transportation for vulnerable groups, emphasizing the need to integrate technological solutions for individuals with reduced mobility (e.g. such as the visually impaired) into digital mobility platforms and land-use planning. The study highlights the lack of focus on rural regions and diverse vulnerable groups, stressing the importance of better integrating technology and land-use planning to improve transportation accessibility.